2022
DOI: 10.1073/pnas.2121273119
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule M1 promotes optic nerve regeneration to restore target-specific neural activity and visual function

Abstract: Axon regeneration is an energy-demanding process that requires active mitochondrial transport. In contrast to the central nervous system (CNS), axonal mitochondrial transport in regenerating axons of the peripheral nervous system (PNS) increases within hours and sustains for weeks after injury. Yet, little is known about targeting mitochondria in nervous system repair. Here, we report the induction of sustained axon regeneration, neural activities in the superior colliculus (SC), and visual function recovery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The signal was then rectified and smoothed by removing the direct current from the raw EMG signal. RMS of EMG amplitude was detected by setting the minimum threshold to 10% above the rising and falling phases of the EMG signal over the time period of 30 s. RMS of EMG amplitude was calculated by taking square root and average of individual points 29,34,35 …”
Section: Methodsmentioning
confidence: 99%
“…The signal was then rectified and smoothed by removing the direct current from the raw EMG signal. RMS of EMG amplitude was detected by setting the minimum threshold to 10% above the rising and falling phases of the EMG signal over the time period of 30 s. RMS of EMG amplitude was calculated by taking square root and average of individual points 29,34,35 …”
Section: Methodsmentioning
confidence: 99%
“…Gene therapy for glaucoma naturally targets the ciliary epithelium [150][151][152], trabecular reticulum cells [153], and RGCs [154][155][156]. The development of gene therapy for glaucoma is predicated based on the ongoing investigation into its pathogenic etiology and disease pathways, with the identification of a novel gene target hinging upon its pivotal role in regulating RGC apoptosis or ON atrophy associated with glaucoma [157,158] The most common genetic disorder in optic neuropathy is Leber's hereditary optic neuropathy (LHON), which is characterized by progressive degeneration of RGCs [159]. A common mitochondrial DNA mutation in the gene encoding NADH dehydrogenase is responsible for about 60%-90% of occurrences in individuals with LHON [160], and LHON is an ideal disease model for gene therapy research due to its substantial patient population and amenability to correction of the underlying genetic defect [109].…”
Section: Gene Therapy For On Injurymentioning
confidence: 99%
“…Gene therapy for glaucoma naturally targets the ciliary epithelium [150–152], trabecular reticulum cells [153], and RGCs [154–156]. The development of gene therapy for glaucoma is predicated based on the ongoing investigation into its pathogenic etiology and disease pathways, with the identification of a novel gene target hinging upon its pivotal role in regulating RGC apoptosis or ON atrophy associated with glaucoma [157, 158]. The CaMKII (calcium/calmodulin protein‐dependent protein kinase II) pathway regulates key cellular processes and functions throughout the body, including those of RGCs.…”
Section: Bridging the Gap: Combating Blindness Worldwide With Regener...mentioning
confidence: 99%
“…The results of these studies point to the direction that by maintaining the microtubule dynamics and promoting axonal transport in sensory neurons could protect the patients from axon degeneration and development of CIPN. Our previous study demonstrated that mitochondrial fusion promoter M1 promoted mitochondrial trafficking in the DRG neurons as well as in sciatic nerves leading to a remarkable axon regeneration (an energy-demanding process that requires robust mitochondrial transport along the regenerating axons) after peripheral nerve and optic nerve injuries ( Au et al, 2022a ).…”
Section: Molecular Mechanisms Underlying the Development Of Cipnmentioning
confidence: 99%